Inhibitory Effect of Triterpenoids from Dillenia serrata (Dilleniaceae) on Prostaglandin E2 Production and Quantitative HPLC Analysis of Its Koetjapic Acid and Betulinic Acid Contents - Juriyati Jalil; Carla W. Sabandar; Norizan Ahmat; Jamia A. Jamal; Ibrahim Jantan; Nor-Ashila Aladdin; Kartiniwati Muhammad; Fhataheya Buang; Hazni Falina Mohamad; Idin Sahidin (Molecules, 2015)
The crude methanol extracts and fractions of the root and stem barks of Dillenia serrata Thunb. showed 64% to 73% inhibition on the production of prostaglandin E2 (PGE2) in lipopolysaccharide-induced human whole blood using a radioimmunoassay technique. Three triterpenoids isolated from the root bark of the plant, koetjapic (1), 3-oxoolean-12-en-30-oic (2), and betulinic (3) acids, exhibited significant concentration-dependent inhibitory effects on PGE2 production with IC50 values of 1.05, 1.54, and 2.59 μM, respectively, as compared with the positive control, indomethacin (IC50 = 0.45 μM). Quantification of compounds 1 and 3 in the methanol extracts and fractions were carried out by using a validated reversed-phase high performance liquid chromatography (RP-HPLC) method. The ethyl acetate fraction of the stem bark showed the highest content of both compound 1 (15.1%) and compound 3 (52.8%). The strong inhibition of the extracts and fractions on cyclooxygenase-2 (COX-2) enzymatic activity was due to the presence of their major constituents, especially koetjapic and betulinic acids.